FAKTOR RISIKO GANGGUAN AKIBAT PENYELAMAN PADA PENYELAM TRADISIONAL DI KARIMUNJAWA JEPARA - Rahmadayanti Rahmadayanti; Budiyono Budiyono; Yusniar Hanani Darundiati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Health problem occurred in the traditional fishermen fieldwork was hyperbaric health problem in which facing high-pressured zone whose compression was more than one atmosphere. The incidence of this disease in Karimun alone in 2003 occurred seven cases of the disease hyperbaric with one person died, 2004 the 7 cases with 2 deaths in 2005 occurred in 10 cases and 3 deaths in 2006 occurred in 4 cases one person died. Cumulatively from 2007 to March 2014 there were 104 cases with 7 deaths. This study aims to determine the relationship of risk factors due to interference on the diver dives traditional in Karimunjawa Jepara. This research uses explanatory survey research with cross sectional design. Sample size was 40 respondents. The results showed 26 of 40 respondents exposed to diseases due dives. Analyzed using univariate and bivariate with Chi Square test. The results showed 12 independent variables studied are four variables associated with a disorder caused dives that work period (p-value = 0.001), the frequency of dives (p-value = 12:02), the depth of the dive (p-value = 0.001) and speed rising to the surface (p-value = 0.001). the 4 variables which was not matched were age (p-value = 0,079), IMT (p-value = 0,868), dive time (p-value = 0,481), surface interval (p-value = 0,168), and the 4 describtive variables were dive duration, APD used, compressor preassure and the depth temperature. The conclusion of this study risk factors associated with impaired as a result of the dives on traditional divers in Karimunjawa Jepara are working period, the frequency of dives, dive depth and the speed rises to the surface. The suggestion is that the Department of Marine Fisheries, facilities can hold to the traditional diver, health centers pay more attention to the health of the divers.